Obtenção e caracterização de farinha de casca de jabuticaba (Plinia cauliflora) para adição em biscoito tipo cookie - Marquetti, Carline (2014)
The jabuticaba is a tropical fruit with important nutritional properties, and excellent source of carbohydrates, fiber, phenolic compounds and minerals like iron, calcium and phosphorus. This fruit and its fractions may have extensive applicability both for industry and for the commercialization and consumption in natura. Research indicates that the greatest fraction of the jabuticaba biologically active species is in the skin, may enable their use for production of a product as an alternative use of the same, enabling the production of foods with functional properties. This allows forward with studies directed to the bioactive compounds present in both the fruit as in derivatives and to evaluate the influence of processing these compounds. Based on the above, the present study aimed to evaluate the bioactive compounds from the jabuticaba skin (Plinia cauliflora) and remaining in the jabuticaba flour skin for later use in biscuit type cookie. The variance between the levels of these compounds in the jabuticaba skin and flour skin were also evaluated. The study was conducted by means of physicochemical analysis of hydroalcoholic extracts of the skin and flour, they being, moisture, protein, lipid, ash, fiber, carbohydrates, calories, total titratable acidity, pH, bioactive compounds (phenols, flavonoids, anthocyanins, condensed tannins) and antioxidant activity by three different methods (DPPH expressed in EC50, DPPH expressed in TEAC and FRAP). The skin has proved to be rich in phenolic compounds, among them, anthocyanins, flavonoids and condensed tannins, reinforcing that the composition showed considerable levels of antioxidant activity in both the scavenging and the interaction with free radicals. Also showed high levels of moisture and considerable content of fiber and carbohydrates. The jabuticaba flour skin showed consistent moisture with legislation and considerable amounts of carbohydrates, overall phenolic compounds and antioxidant activity, besides being a source of fiber. It is also noted there in the concentration of the analyzed compounds due to dehydration of the skins and other factors. From flour, biscuits type cookie were prepared with substitutions of 0.0, 2.5, 5.0 and 7.5% whole wheat flour for jabuticaba skin flour and they assessed physicochemical form with the same variables used in the skin and flour. Subsequently were evaluated microbiologically before being forwarded to the sensory analysis, already approved by the Ethics Committee, where acceptance and purchase intent tests were performed. Cookies obtain moisture levels consistent with the law, apart from revealing the source of protein and fiber. All formulations showed reduction in the concentration of bioactive compounds due to the cooking process, but also there was maintenance of desirable levels of phenolics and antioxidant activity. Sensory results showed that all samples were accepted, compared to the standard. The formulation with 7.5 % jabuticaba skin flour was considered ideal for adding in biscuits type cookie, as showed higher content of phenolic compounds and also in higher levels of antioxidant activity, resulting in products with high content of biologically active properties without interfering with the sensory quality and standards of identity.